Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Joo Acuña, María Gabriela (2019)
The following paper is an analysis of a Company that belongs to the Peruvian Agribusiness industry. Following that, we were able to recognize the situation of the Company and give examples of potential strategies. This was done to show our knowledge in the field of administration and business. The Business model, the value chain and the basis of the competitive advantage were some of the concepts of analysis. Camposol is a Company that not only is a producer of fruits, vegetables and seafood but it also commercializes these products and that is exactly the most important aspect of its competitive advantage.